GE_GERICHTE P/9105/2020 vom 22. April 2023 - GE Cour de justice (2023)
IN DUBIO PRO REO;CONFRONTATION;ACTE D'ORDRE SEXUEL AVEC UN ENFANT;TORT MORAL;CONTRAINTE SEXUELLE | CP.187; CP.189; CPP.147; CPP.154